(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This article examines the ecological status of water bodies through the integrated use of bioindicator organisms as a reliable tool for environmental monitoring. The relevance of the study is determined by the increasing anthropogenic pressure on aquatic ecosystems, including chemical pollution, eutrophication, habitat transformation, and hydrological disturbances, all of which directly affect biodiversity and water quality. In contrast to purely physicochemical assessment methods, bioindication makes it possible to identify long-term ecological changes by analyzing the composition, abundance, diversity, and sensitivity of aquatic organisms to environmental stressors. Special attention is given to phytoplankton, zooplankton, benthic macroinvertebrates, aquatic plants, and fish as the principal bioindicator groups reflecting the trophic state, oxygen regime, toxic contamination, and general ecological stability of water bodies. The article substantiates the importance of combining hydrobiological observations with laboratory and field methods in order to obtain objective and representative data on the condition of aquatic environments. The study also considers the methodological foundations of biological monitoring, including sampling procedures, taxonomic identification, index-based assessment, and interpretation of indicator responses under different pollution levels. It is shown that the use of bioindicator organisms improves the accuracy of ecological diagnostics, supports early detection of degradation processes, and contributes to scientifically grounded water management decisions. The practical significance of the research lies in the possibility of applying bioindication approaches in the monitoring of rivers, canals, reservoirs, ponds, and other freshwater ecosystems, especially in regions with intensive agricultural and industrial development. The findings confirm that biological monitoring is an essential component of sustainable management, conservation of aquatic biodiversity, and maintenance of ecological balance in water bodies.